Plasma cortisol suppression response in the South African black population with glaucoma. - Freedman, J (1976)
Plasma cortisol suppression was measured in 25 Black glaucomatous patients and in 19 Black patients of similar age and sex, but without glaucoma, who acted as controls. Initial serum cortisol levels were found to be slightly higher in the glaucomatous group. The response to systemically-administered cortisone was statistically more marked in the glaucomatous patients compared with the control group.